A Passion Narrative Synopsis in Codex Climaci Rescriptus: A New Edition Based on Multispectral Images - Malik, Peter (The journal of theological studies, 2025)
This article presents an edition of the Passion Narrative Synopsis in Codex Climaci Rescriptus. The edition is based on the post-processed multispectral images, produced by Early Manuscripts Electronic Library in cooperation with the Lazarus Project. The new technology has aided in uncovering substantial, hitherto unseen textual and paratextual elements as well as correcting various errors in the editio princeps. Moreover, the results of radiocarbon analysis have been factored into the dating of the fragment, resulting in a new proposal for its date of origin.